Early cardiac events after haploidentical hematopoietic cell transplantation with post-transplant cyclophosphamide. subanalysis exploring cardiac toxicity conducted on behalf of GETH-TC - Pinto, Filipe R.; Cascos, Enric; Pérez-López, Estefanía; Baile-González, Mónica; Martín Rodríguez, Carlos; Pascual Cascón, María Jesús; Luque, Marta; Esquirol, Albert; Calvo, Carmen Martín; Peña-Muñóz, Felipe; Fernando, Inmaculada Heras; Oiartzabal Ormtegi, Itziar; et al. (Frontiers in Immunology, 2025)
IntroductionHaploidentical allogeneic hematopoietic cell transplantation (haplo-HCT) using post-transplant cyclophosphamide (PTCY) has become a standard approach for patients lacking HLA-matched donors. While effective in reducing graft-versus-host disease (GVHD), concerns about PTCY-associated cardiovascular toxicity remain. This study investigates the incidence, predictors, and impact of early cardiac events (ECE) in haplo-HCT recipients.MethodsWe conducted a retrospective, multicenter analysis of 268 patients with acute myeloid leukemia (AML) treated with anthracycline-based induction regimens and undergoing their first haplo-HCT with PTCY (50 mg/kg/day on days +3 and +4) between 2011 and 2022. ECEs, defined as any new cardiac event within 100 days post-transplant, were analyzed using cumulative incidence functions considering death and relapse as competing risks. Risk factors and the impact on non-relapse mortality (NRM) and overall survival (OS) were assessed via univariate and multivariate regression models.ResultsThe median patient age was 57 years (range: 18–79), and pre-transplant comorbidities included hypertension (22.4%), dyslipidemia (13.1%), diabetes mellitus (6.7%), and prior cardiac history (14.2%). ECEs occurred in 23 patients (8.6%) at a median of 19 days post-transplant (IQR: 5–66), with a day +100 cumulative incidence of 8.6% (95% CI: 6.1–12.3). The most frequent complications were pericardial effusion/pericarditis (43.5%), arrhythmias (30.4%), and heart failure (17.4%). Severe ECEs (CTCAE grade 3–4) were observed in 30.4% of cases, and four deaths (17.4%) were directly attributed to ECEs. Univariate analysis identified dyslipidemia (HR: 3.87, p=0.001), hypertension (HR: 2.76, p=0.015), and moderate-severe veno-occlusive disease (HR: 4.94, p=0.002) as significant predictors of ECE. ECEs were associated with lower OS (HR: 1.78, p=0.04) and higher NRM (HR: 2.87, p=0.005).DiscussionWhile the incidence of ECEs following haplo-HCT with PTCY was relatively low, their occurrence significantly worsened transplant outcomes. These findings underscore the importance of cardiovascular risk assessment and structured cardiac monitoring to mitigate complications in haplo-HCT recipients.